Formulation of a radiological scoring system to prognosticate patients with primary intracerebral haemorrhage (Journal of Medical Science, 2023)
Background. Primary intracerebral haemorrhage is a neurological condition associated with high morbidity and mortality. Outcome prediction is necessary to allocate the available resources in such cases judicially. Our study aims to identify the radiological predictors of in-hospital mortality based on a plain CT study of the brain at admission and to develop a prognostic scoring system based on them. Material and methods. We collected the clinical and radiological data from 182 consecutive patients who presented with primary spontaneous ICH. Bivariate analysis of radiological predictors of in-hospital mortality was undertaken using unadjusted logistic regression. Those variables found to have significance were put into a multivariate logistic regression model. The Results of multivariate logistic regression were treated as a foundation for developing the scoring system. Results. The mortality rate in our series was 23.6% (N = 43). After multivariate analysis, Midline shift (MLS), presence or absence of intraventricular haemorrhage (IVH), Volume of ICH and Location of haematoma were significant predictors of mortality. Based on the identified radiological variables, a five-score prognostic scoring system (AUROC = 0.925, 95% CI 0.887–0.964)) was developed, with higher scores indicating higher mortality. Conclusions. The established scoring system, MIVL, may help physicians to do better patient counselling regarding outcomes.